ANALISIS RPP BIOLOGI BERDASARKAN KURIKULUM 2013 DI SMA NEGERI SE-KABUPATEN ACEH SELATAN - Khairil Hadi (LPPM Universitas Cipta Mandiri, 2021)
AbstractThe aims of this research are to know the quality of biology lesson plans based on Curriculum 2013 at State Senior High Schools of South Aceh district. The population of this reseach was biology teachers who teach tenth grade in South Aceh district and the samples were twenty biology teachers that was taken from each school. This research used the descriptive method with instruments of RPP document that have validated by validators. Research data was taken from document of 20 biology lesson plans based on Curriculum 2013. The result of research showed that the quality of biology lesson plans based on Curriculum 2013 at State Senior High Schools in South Aceh district belong to enough criteria (75,68%). Biology teachers at State Senior High Schools of South Aceh district still constrained formulate subject matter, affectif instruments form, and psycomoric instruments form.